Between Expectation and Reality: Tourists' Perceptions of Service Quality at Cikole Luwak Coffee Agrotourism Using the SERVQUAL Approach: Antara Ekspektasi dan Realitas: Persepsi Kualitas Layanan Wisatawan di Agrowisata Kopi Luwak Cikole Menggunakan Pendekatan SERVQUAL - Dani Adiyanto; Adam Maulana; Moch Mozza Aditya Aryanto; Ahmad Rizki Ageng Afani; Sumartik Sumartik (Procedia of Social Sciences and Humanities, 2026)
General Background: The home industry food sector, particularly cookie production, represents a continuously expanding segment of small and medium enterprises in Indonesia. Specific Background: J&C Cookies operates as a prominent home-industry cookie producer in Bandung, managing domestic and export distribution while preparing for professionalized management. Knowledge Gap: Existing literature exhibits inconsistent findings regarding the relationship between marketing mix elements and customer satisfaction, necessitating a comprehensive strategic positioning framework. Aims: This study aims to formulate a strategy to improve customer satisfaction at J&C Cookies by analyzing product quality, packaging, price, and service quality using a qualitative SWOT approach. Results: Evaluation yields an Internal Factor Analysis Summary score of 2.82 and an External Factor Analysis Summary score of 2.45, positioning the firm in Quadrant V of the Internal-External matrix to hold and maintain. Novelty: This research uniquely integrates internal marketing mix evaluations with SWOT, IFAS-EFAS, and IE matrices for a growing cookie home industry enterprise approaching professionalization. Implications: Management should prioritize product and packaging differentiation combined with digital service strengthening to improve customer satisfaction and competitive advantage. Highlights: Taste consistency and brand reputation serve as dominant internal strengths for the cookie enterprise. Matrix evaluations place the business in the hold and maintain position requiring defensive and growth strategies. Recommended actions prioritize product differentiation and packaging upgrades alongside digital service improvements. Keywords: Customer Satisfaction, Product Quality, Packaging, Price, SWOT Analysis